0 تصويتات
22 مشاهدات
بواسطة
حل المعادلة ٣-٦س+٨س=٩

1 إجابة واحدة

0 تصويتات
بواسطة
الحل:
3 - 6س + 8س = 9
نجمع المتغيرات معًا:
2س = 6
نقسم الطرفين على 2:
س = 3
إذاً الحل للمعادلة هو س = 3.

اسئلة متعلقة

0 تصويتات
1 إجابة 25 مشاهدات
0 تصويتات
1 إجابة 25 مشاهدات
سُئل أبريل 23، 2024 بواسطة مجهول
0 تصويتات
1 إجابة 31 مشاهدات
سُئل أبريل 20، 2024 بواسطة مجهول
0 تصويتات
1 إجابة 34 مشاهدات
سُئل أبريل 23، 2024 بواسطة مجهول
0 تصويتات
1 إجابة 26 مشاهدات
سُئل أبريل 23، 2024 بواسطة مجهول
حلول -------- حفظ.com
...